Strategi Menumbuhkan Karakter Jujur Pada Siswa Sekolah Dasar Melalui Materi Pelajaran Panca Sradha - Wijaya, I Made Tisnu (Adi Widya: Jurnal Pendidikan Dasar, 2017)
Honesty is a very significant thing to grow in elementary school age children. It is because at this age the child should be given moral lessons. For that lesson of Hindu religion as one to grow the honest character must be able to realize it. One lesson that can be used as media to foster the honest character is on the subject matter of Panca Sradha. However, during this lesson the Hindu religion related to the material of Panca Sradha still in a discourse level. As is known, the discussion on the material of Panca Sradha emphasizes on the belief aspects of learners to God, Atma, Karma Phala, Punarbhawa and Moksa. The five basic beliefs in the teachings of Hinduism are indeed difficult to explain with the media especially in the students who are still in elementary school level. For this reason, this paper will provide a solution that can be used as a handle of Hindu teachers in elementary schools in elaborating the subject matter of Panca Sradha to foster an honest character in elementary school students.